Optimization of Electricity Generation Schemes in the Java-Bali Grid System with Co2 Reduction Consideration - Farizal, Farizal; Septia, Wenty Eka; Rachman, Amar; Nasruddin, Nasruddin; Mahlia, Teuku Meurah Indra (UI Scholars Hub, 2016)
This research considers the problem of reducing CO2 emissions from the Java-Bali power grid system that consists of a variety of power-generating plants: coal-fired, natural gas, oil, and renewable energy (PV, geothermal, hydroelectric, wind, and landfill gas). The problem is formulated as linear programming and solved using LINGO 10. The model was developed for a nation to meet a specified CO2 emission target. Two carbon dioxide mitigation options are considered in this study, i.e. fuel balancing and fuel switching. In order to reduce the CO2 emissions by 26% in 2021, State Electric Supply Company (PLN) has to generate up to 30% of electricity from renewable energy (RE), and the cost of electricity (COE) is expected to increase to 617.77 IDR per kWh for a fuel balancing option, while for fuel switching option, PLN has to generate 29% of electricity from RE, and the COE is expected to increase to 535.85 IDR per kWh.